Analisis Kandungan Kualitas Air Laut Pantai Wisata Batu Gong Untuk Wisata Bahari Kecamataan Lalonggasumeeto Kabupaten Konawe - Asmita, Asmita; Assiddieq, Moch.; Ndibale, Wa (Universitas Muhammadiyah Kendari, 2022)
Indonesia is a developing country that actively leads development in all areas of life, one of which is the economic sector. Economic development in Indonesia is growing rapidly along with the advancement of information systems that are rapidly changing with the times. With the increasing pace of development. Therefore, this study was conducted aiming to determine the quality of sea water at Batu Gong beach, Lalonggasumeeto District, Konawe Regency in terms of physical, chemical parameters and analyze the suitability of marine tourism on Batu Gong beach, Lalonggasumeeto District, Konawe Regency in terms of water quality. The results of this study are the Batu Gong beach area on three water quality parameters that exceed the sea water quality standard for marine tourism quality standards in accordance with the Decree of the Minister of the Environment number 51 of 2004, namely the brightness at 15.00 which 2nd exceed quality standards. the temperature at 10.00 is 24°C, at 12.00 it is 26°C, at 15.00 it is 27°C exceeding the quality standard. TSS at 10.00 is 2486.66 TSS at 12.00 is 2506.66 TSS at 15.00 is 3093.33 exceeds the quality standard and in the coastal waters of Batu Gong does not exceed the sea water quality standard for marine tourism in accordance with the Decree of the Minister of the Environment number 51 of 2004.